Incidence of Aflatoxin B1, B2, G1, G2 in Spices Marketed in Karachi, Pakistan - Raza, Rashid; Liaquat, Anum; Ayaz, Areeba; Sarwar, Farkhanda; Khan, Hania Amin; Kisa-e-Zehra; Khan, Farha Irshad (Journal of Research (Science), 2025)
Aflatoxins form one of the vital groups of mycotoxins. Aflatoxins are one of the highly poisonous secondary metabolites of A. flavus and A. parasiticus. In the current study aflatoxinaAFB1, AFB2, AFG1 and AFG2 contamination in the spices purchased from local market located at all five towns of Karachi, Pakistan; have been analyzed using standard method of analysis (HPLC) technique. A total of 360 samples of spices were tested for each aflatoxin. 57 of the spices samples were detected as positive for aflatoxin B1, 52 samples were found to be contaminated with AF B2, 35 samples of spices were being tested as positive with AFG1. Whereas Aflatoxin G2 was found to be absent in all samples. Maximum level of aflatoxin B1 was detected as 8.3 – 20.62ppm in turmeric and minimum level was found in coriander that is 0.66 – 0.98ppm. Maximum level of aflatoxin B2 was detected as 9.8 – 19.64ppmin turmeric and minimum level was found in coriander that is 0.48 – 1.0ppm. Maximum level of aflatoxin B1 was detected as 1.22 – 6.46 in red chili and minimum level was found in black pepper that is 1.42 – 2.54ppm. Most of the samples (109 out of 360) in the currents study found to contain aflatoxin within the threshold limit set for aflatoxin B1. It can be concluded that the most of the spices marketed in Karachi are safe for consumption. The high levels of aflatoxin in spice samples detected in the period of studies could be a serious risk to human health in the largest populated city of Pakistan, where limited resources are available for the prevention and controlling their levels in the food supply.